Pembinaan Mental Keagamaan Anak melalui Pelestarian Nilai-Nilai Agama Islam di SMP Negeri 1 Kudu Jombang - Ahmad Dalail; Mardiyah (Universitas Hasyim Asy'ari (UNHASY) Tebuireng Jombang, 2019)
There is a degradation of students' morality and morality which is increasing over time in society, which in turn forms habits that are not in line with religious guidance. In addition, the low religious mentality of children is also a driving force for the increasing moral degradation of students, so religious mental fostering is very necessary, especially in educational institutions. Both in Islamic educational institutions, as well as in general education institutions. The focus of this research is divided into three, namely how to develop the mental religion of children in SMP Negeri 1 Kudu Jombang, how to preserve Islamic religious values ​​and what are the inhibiting factors or obstacles in the mental religious development of children at SMP Negeri 1 Kudu Jombang. The purpose of this study was to identify, describe, and analyze the Religious Mental Development of Children through the Preservation of Islamic Religious Values ​​Case Studies at SMP Negeri 1 Kudu Jombang. This type of research is a qualitative field, with a descriptive approach because this research only reveals and describes the data as it is based on facts that arise or occur at the time the research was carried out. The presence of researchers as non-participants. Data collection techniques by means of observation, documentation, and interviews. In this case the researcher will collect data about the Religious Mental Development of Children through the Preservation of Islamic Religious Values ​​Case Study at SMP Negeri 1 Kudu Jombang. Data analysis techniques use domain analysis. Checking the validity of the data through extension of observations, persistence of observations, referential adequacy and member checks. For the research results of the title Religious Mental Development of Children through Preservation of Islamic Religious Values ​​Case Study of SMP Negeri 1 Kudu Jombang is trying to foster and shape the mental religion of children through the preservation of Islamic religious values, namely Rahman value, Rahim value, piety value, and obedience. What is grown through the habituation of tawadhu to the teacher, accustomed to praying dhuha and praying five times a day, and accustomed to reading the Al-Qur'an